2023
DOI: 10.3390/metabo13101040
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Indoor Microbiome and Metabolites in Shaping Children’s Nasal and Oral Microbiota: A Pilot Multi-Omic Analysis

Mei Zhang,
Hao Tang,
Yiwen Yuan
et al.

Abstract: Maintaining a diverse and well-balanced nasal and oral microbiota is vital for human health. However, the impact of indoor microbiome and metabolites on nasal and oral microbiota remains largely unknown. Fifty-six children in Shanghai were surveyed to complete a questionnaire about their personal and environmental characteristics. The indoor microbiome and metabolites from vacuumed indoor dust were profiled via shotgun metagenomics and untargeted liquid chromatography-mass spectrometry (LC–MS). The nasal and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 60 publications
0
1
1
Order By: Relevance
“…A majority of the microbial taxa identified in this study has not been reported in previous indoor microbiome and rhinitis/asthma studies (Fu et al, 2020b;Fu et al, 2022;Fu et al, 2023a;Sun et al, 2023;Zhang et al, 2023b). Several reasons could underlie this discrepancy.…”
Section: Potential Protective and Risk Microbial Taxa Of Rhinitiscontrasting
confidence: 66%
“…A majority of the microbial taxa identified in this study has not been reported in previous indoor microbiome and rhinitis/asthma studies (Fu et al, 2020b;Fu et al, 2022;Fu et al, 2023a;Sun et al, 2023;Zhang et al, 2023b). Several reasons could underlie this discrepancy.…”
Section: Potential Protective and Risk Microbial Taxa Of Rhinitiscontrasting
confidence: 66%
“…Another comparative analysis revealed that the low sequencing accuracy of PacBio may impair its taxonomic resolution in the study of human gut microbiota [88]. Nevertheless, PacBio sequencing has been successfully used in several metagenomic studies and was able, for example, to identify the microbiome profiles of heavy-metal-contaminated soils [89], analyze extrachromosomal genetic elements (mainly plasmids) in the human gut [90], characterize the airway microbiome of chronic obstructive pulmonary disease patients [91], identify low-biomass human gut phageomes [92], and highlight the association between the indoor microbiome and nasal/oral humans microbiome [93]. A very recent paper by Eisenhofer and colleagues compared shotgun metagenomics carried out with both NGS and PacBio technologies and found that even if PacBio ameliorates the quality of bacterial genome assembly, it is more expensive and needs a higher sequencing coverage with respect to short reads, thus suggesting that the most optimal strategy depends on the aims of each specific project [94].…”
Section: Metagenomicsmentioning
confidence: 99%